2018
DOI: 10.1016/j.envpol.2018.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Short-term transcriptome and microRNAs responses to exposure to different air pollutants in two population studies

Abstract: Diesel vehicle emissions are the major source of genotoxic compounds in ambient air from urban areas. These pollutants are linked to risks of cardiovascular diseases, lung cancer, respiratory infections and adverse neurological effects. Biological events associated with exposure to some air pollutants are widely unknown but applying omics techniques may help to identify the molecular processes that link exposure to disease risk. Most data on health risks are related to long-term exposure, so the aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 85 publications
(86 reference statements)
0
19
0
Order By: Relevance
“…MicroRNAs (miRNA or miRs) are non-coding RNAs that regulate the expression of target genes by inhibiting the translation or degredation of mRNA (9). miRNAs are involved in the regulation of metabolism, the inflammatory response, heart-associated diseases, organ transplantation and cancer by regulating mRNA and protein expression (9,10). Among all miRNAs that regulate the progression of inflammation, the role of miR-146a is prominent.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNA or miRs) are non-coding RNAs that regulate the expression of target genes by inhibiting the translation or degredation of mRNA (9). miRNAs are involved in the regulation of metabolism, the inflammatory response, heart-associated diseases, organ transplantation and cancer by regulating mRNA and protein expression (9,10). Among all miRNAs that regulate the progression of inflammation, the role of miR-146a is prominent.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we used RNA sequencing to identify the DE miRNAs in the embryos from the air pollution-exposed group. Our results showed that a total of 291 miRNAs (204 downregulated and 87 upregulated) Previous references suggested that miRNAs may act crucial roles in the pathogenesis and development of air pollution-induced diseases (Espín-Pérez et al, 2018;Quezada-Maldonado, Sánchez-Pérez, Chirino, Vaca-Paniagua, & García-Cuellar, 2018). For instances, He et al performed miRNA profile to show that miR-155 expression was shown to be an important regulator in the polycyclic aromatic hydrocarbons (PAHs) treatment.…”
Section: Discussionmentioning
confidence: 62%
“…These alterations are initially adaptive, aimed at activating defensive processes counteracting the damage induced by environmental pollutants such as DNA repair, mutation silencing, and apoptosis. However, whenever the environmental exposure lasts for decades, microRNA alterations become irreversible and commit cells to the occurrence of lung cancer environmental risk factors, inducing specific alterations in the microRNA machinery depending on the specificity of the environmental pollutant involved [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Accordingly, microRNA alteration is more predictive of lung cancer occurrence than genomic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the early diagnosis of lung cancers using miR-33a-5p and miR-128-3p signatures has being proposed, as they are linked to tumor suppression processes. [ 9 ] Different response to air pollutants as particulate matter, ultrafine particles, nitrogen oxides, black carbon, and carbon oxides (CO and CO 2 ) may be related to a different expression of miR-92a-3p, miR-484, and miR-186-5p, linking traffic-related exposure to disease risk [ 10 ]. It is known that microRNA and other molecular alterations (oncogene mutations, DNA adducts, transcriptional silencing activation, and proteosome alteration) induced by environmental pollution are quite specific, as each pollutant preferentially alters the expression of a cluster of identifiable molecular fingerprints [ 11 ].…”
Section: Introductionmentioning
confidence: 99%